Retrospective evaluation of combined mycophenolate mofetil and prednisone treatment for meningoencephalomyelitis of unknown etiology in dogs: 25 cases (2005–2011). (12th October 2015) - Barnoon, Itai; Shamir, Merav H.; Aroch, Itamar; Bdolah‐Abram, Tali; Srugo, Itai; Konstantin, Lilach; Chai, Orit
Abstract: Objective: To evaluate the use of a combined protocol of prednisone and mycophenolate mofetil (MMF) for the treatment of meningoencephalomyelitis of unknown etiology (MUE) and to describe response, adverse effects, and outcome. Design: Retrospective study (2005–2011). Setting: University teaching hospital. Animals: Twenty‐five client‐owned dogs with clinical signs, neuroimaging, and cerebrospinal abnormalities consistent with MUE. Five dogs whose MMF treatment was discontinued after 7–14 days due to gastrointestinal clinical signs were evaluated only for adverse effects. Interventions: Dogs were initially treated with prednisone 2 mg/kg PO every 12 hours and with MMF 20 mg/kg PO or IV every 12 hours. Prednisone was tapered after 4 days to 1 mg/kg every 12 hours for 14 days, then to every 24 hours for 30 days, and again reduced by half every 2–4 months thereafter. When prednisone was tapered completely or to 0.5 mg/kg every 24–48 hours without clinical relapse, MMF was tapered in a similar manner. Measurements and Main Results: Partial or complete clinical response was achieved in 95% (19/20) of the dogs. Median survival time by the end of the study was 250 days (range 6 to >1, 679) with 40% (8/20) of the dogs still alive (336–1, 679 days after diagnosis). All Pug dogs (4/20) included in the study died with a median survival time of 14 days. Adverse effects attributed to MMF, which included hemorrhagic diarrhea within the first 2 weeks of treatment, were recorded in 20% (5/25) of the dogs. Conclusions: MMF can be used as an adjunctive treatment for dogs with MUE. This protocol enables reduction of prednisone treatment or, in some cases, its complete withdrawal. The possibility of intravenous administration is advantageous in cases with severe neurological abnormalities and mentation changes, often seen in MUE. Attention is warranted for gastrointestinal adverse effects, especially in the first 2 weeks of treatment.